Spontaneous closure of patent ductus arteriosus in preterm babies after failed attempts at transcatheter device closure - Ahmed Deniwar; Matthew Brown; Duraisamy Balaguru (Wolters Kluwer Medknow Publications, 2022)
Transcatheter closure of patent ductus arteriosus (PDA) for preterm infants is increasingly performed after the Food and Drug Administration approval of the Amplatzer Piccolo Occluder device (Abbott Inc., Abbott Park, IL, USA) in the United States. We report three babies in whom transcatheter closure of PDA was unsuccessful; however, the PDA closed spontaneously in 1-5 days after the transcatheter attempt. The PDA remained closed during follow-up at 3 weeks, 10 weeks, and 17 months, respectively. Mechanical stimulation of the PDA by the wire during attempted device closure likely induced the PDA closure. Further studies are needed to evaluate whether this is a useful alternative therapy in this patient population.